E-NOTULEN RAPAT DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Achmad Behori; Badrul Alamin (Department of Science and Technology Ibrahimy University, 2018)
The process of recording the results of meetings conducted by the notulen of the meeting and then copy back the results of meetings decision into Ms.Word causes doubled the work, the delivery model of meeting results still requires a long process so that socialize well which certainly takes quite a long time. In addition, at the meeting results of its realization could not reach the lowest level of management of the boarding schools, so many 'umana (caretaker) that sometimes do not know the of meeting results that have been approved by a caregiver . To resolve this problem need a special system to improve management of the meeting results, so that in practice the meeting results may socialize well and real-time. On this research proposed by using the design of the system development life cycle SDLC model, i.e. (Systems Development Life Cycle). This model is used in order to be on the design of this e-notulen meeting can be made with the needs of users and in accordance with the rules of development of the system. The proposed system will be created with web based programming language PHP and the MySQL database. The system is expected to help the workload of the meeting (Secretary) and document well the meeting results, give notification of the schedule of meetings and resolutions of the meeting can be easily socialize to each line with a good, fast and accurate. The results of this research is with the applied system